Kindred ebook A graphic novel adaptation. - Butler, Octavia E. (2017)
Octavia E. Butlerâs bestselling literary science-fiction masterpiece, Kindred , now in graphic novel format. Â  More than 35 years after its release, Kindred continues to draw in new readers with its deep exploration of the violence and loss of humanity caused by slavery in the United States, and its complex and lasting impact on the present day. Adapted by celebrated academics and comics artists Damian Duffy and John Jennings, this graphic novel powerfully renders Butlerâs mysterious and moving story, which spans racial and gender divides in the antebellum South through the 20th century.Â  Â  Butlerâs most celebrated, critically acclaimed work tells the story of Dana, a young black woman who is suddenly and inexplicably transported from her home in 1970s California to the preâCivil War South. As she time-travels between worlds, one in which she is a free woman and one where she is part of her own complicated familial history on a southern plantation, she becomes frighteningly entangled in the lives of Rufus, a conflicted white slaveholder and one of Danaâs own ancestors, and the many people who are enslaved by him. Â  Held up as an essential work in feminist, science-fiction, and fantasy genres, and a cornerstone of the Afrofuturism movement, there are over 500,000 copies of Kindred in print. The intersectionality of race, history, and the treatment of women addressed within the original work remain critical topics in contemporary dialogue, both in the classroom and in the public sphere. Â  Frightening, compelling, and richly imagined, Kindred offers an unflinching look at our complicated social history, transformed by the graphic novel format into a visually stunning work for a new generation of readers.